THE INFLUENCE OF TAXPAYER AWARENESS, TAX SERVICE QUALITY, AND MSME TAXPAYER COMPLIANCE ON TAX REVENUE AT KUPANG PRATAMA TAX SERVICE OFFICE - Naiola, Fransiscus Nicodemus; Mudamakin , Agnes K. B.; Tanan, Eugenia H.P.; Gah, Tiffany N.P. (LPPM Universitas Bina Bangsa, 2025)
Purpose — The purpose of this study is to determine how tax revenue at the Kupang Pratama Tax Service Office is impacted by taxpayer knowledge, the quality of tax services, and MSME taxpayer compliance. Method —This quantitative descriptive research utilizes a questionnaire-based data collection approach distributed online through Google Forms at the Kupang Pratama Tax Service Office. These objects or subjects have specific attributes and characteristics. 615 Micro, Small, and Medium-Sized Businesses that were registered as taxpayers at the Kupang Pratama Tax Service Office, which is situated on Jl. Palapa No. 8, Oebobo, Oebobo, Kupang City, East Nusa Tenggara, were the study's population. Result — This study reveals that there is no relationship between the taxpayer awareness variable and tax revenue, tax revenue is impacted by the tax service quality variable. Additionally, tax income is unaffected by the taxpayer compliance variable.